The method of cycle-slip detection and repair GNSS meaturements by using receiver with high stability frequency oscillator - KOSAREV, Nikolai S.; ANTONOVICH, Konstantin M.; LIPATNIKOV, Leonid A. (Contributions to Geophysics and Geodesy, 2019)
A method of phase GNSS measurement control is described. The method is based on comparison of geometric range increments which are calculated using measurement data and approximate receiver coordinates and satellite navigation message position taking into account troposphere and ionosphere correction increments. Applicability of moving average for phase GNSS measurement control to detect the cycle slips and outliers is demonstrated. Test results of cycle slip detecting in phase measurements made by the receiver with high stability frequency oscillator are provided.